Inspections of Hydro-Geotechnical on Ngancar Dam - asmaranto, runi; Suryono, Antonius; Hidayat, Muhammad Nurjati (Civil and Environmental Science Journal (CIVENSE), 2019)
Besides having great benefits, dam also holds enormous potential dangers. The collapsed dam will cause devastating flood along the river resulting in loss of lives, properties, damage to public facilities and environment, especially in the downstream area. For safety and prevent the occurrence of the disaster, the operational of dam should always be monitored, inspected and maintained properly continually. With a good monitoring, dam managers will discover as early as possible the problems emerging in the dam, and then perform the appropriate steps to prevent the development of the problems. This paper will perform hydro-geotechnical analysis as a review current condition of slope stability based on the result of soil investigation on present dam condition and review instrumentations installed in Ngancar Dam